23. Translation and cross-cultural adaptation of the Sleep-Related Breathing Disorder scale of the Pediatric Sleep Questionnaire into Vietnamese language - Le, Nguyen Ngoc Quynh; Huong, Nguyen Thi Thanh; Trang, Le Huyen; Huong, Nguyen Mai; Lien, Luong Thi; Hau, Trinh Thi; Cong, Mai Thanh; Mai, Nguyen Thi Thanh (Tạp chí Nghiên cứu Y học, 2023)
Objective: The Pediatric Sleep Questionnaire (PSQ) has shown to be a valuable screening tool with good sensitivity and specificity for obstructive sleep apnea among children. Our aim was to cross-culturally translate and adapt the PSQ into Vietnamese language for clinical and research using. Methods: The Vietnamese version of the SRBD-PSQ was translated by the University of Michigan, which reserves the copyrights. The adapted questionnaire was applied to parents of 60 children aged 6 - 14 years. The reliability of the translated questionnaire was measured by Cronbach α, Pearson correlation and Kappa statistics. Results: Vietnamese PSQ has shown high internal consistency by Cronbach’s α (0.781 for the total test, 0.745 for subscale “snoring”, 0.682 for “sleepiness”, 0.763 for “behaviour”). Test-retest reliability for all items presented a good correlation, with the Kappa statistic ranged between 0.498 and 0.832. Conclusion: The Vietnamese version of PSQ has sufficient reliability and validity to measure obstructive sleep apnea outcome and showed to be linguistically accurate and acceptable for use among Vietnamese children.